DOP54 Identification and development of a 1st in class naturally-derived protein that drives mucosal healing and is orally delivered by an engineered cellular therapy targeting the gastro-intestinal tract. (21st January 2022) - Shilova, I; La Chat, C; Nigatu, E; Messner, E; Desnoyer, J; Willcoxon, M; Banas, S; Ravichandar, D; Narayan, N; DeSantis, T; Dabbagh, K; Yamamoto, L
Abstract: Background: In Inflammatory Bowel Disease (IBD), intestinal barrier dysfunction and epithelial cell injury are believed to be associated with activation of the immune system to drive disease-associated inflammation, which together constitute key features of active disease. Existing drugs used to treat IBD induce endoscopic remission and improvements in mucosal healing in only a minor proportion of patients, driving a critical need for therapies which lead directly to mucosal healing. Furthermore, predicting patients who may benefit from therapeutics that address specific mechanisms of mucosal healing may augment response rates. Methods: We screened proteins, identified from a meta-analysis of healthy human microbiome, in cellular assays and animal models related to mucosal injury, with the goal of identifying novel therapeutics that have the potential to directly induce mucosal healing. The proteins identified were further optimized by protein engineering to increase their stability as well as gastro-intestinal (GI) targeting via oral administration. For this, therapeutic proteins were expressed using a probiotic, Lactococcus lactis (L.lactis), engineered to display the recombinant proteins on the cell surface, and evaluated for activity in DSS- and DNBS-induced models of colitis in mice. Mechanism of action studies using computational and laboratory based methods to analyze gene expression and direct molecular interactions with human proteins, enabled the identification of pathways modulated by the candidate molecules. These pathways were further evaluated for their ability to identify biomarkers in specific patients most suitable for treatment in a precision medicine approach. Results: We have identified a novel, healthy microbiome-derived protein that demonstrated robust activity in human epithelial injury assays in vitro. The protein reduced intestinal injury related pathology in mice when orally administered to target directly the GI tract. SG-5-00455, the product based on an L.lactis strain expressing the candidate therapeutic protein, reduced pathology scores, inflammation and barrier function related LPS-binding protein levels to levels comparable to those obtained glucagon-like peptide 2 (GLP-2), as well as improving dysregulated tissue repair and fibrosis-associated gene expression and proteins levels. SG-5-0455 treatment did not result in systemic exposure, driving its therapeutic activity in a GI-localized manner by targeting pathways related to tissue injury and fibrinolysis. Conclusion: SG-5-00455, through its novel mechanism of action and oral delivery to directly target tissue repair pathways in the GI-tract, offers the potential to address a large critical need in IBD.